Ambient concentration and dry deposition of major inorganic nitrogen species at two urban sites in Sichuan Basin, China. (December 2016) - Wang, Huanbo; Yang, Fumo; Shi, Guangming; Tian, Mi; Zhang, Leiming; Zhang, Liuyi; Fu, Chuan
Abstract: To assess pollution levels of major inorganic nitrogen species and their atmospheric deposition input to sensitive ecosystems in Sichuan Basin, southwest China, ambient concentrations of oxidized (NOy ∼ NO2, HNO3, NO3 − ) and reduced (NHx = NH3, NH4 + ) nitrogen species were collected at two urban sites during four one-month periods, each in a different season from July 2014 to April 2015. Estimated annual mean concentration of NOy was 20.3 and 13.5 μg N m −3 in Chengdu and Wanzhou, respectively, and NHx was 16.9 and 13.6 μg N m −3, respectively. Back trajectory cluster analysis indicated that high levels of NOy and NHx in Chengdu were mainly caused by local emissions while those in Wanzhou were caused by both the local emissions and long-range transport of pollutants. On annual basis, NO2 contributed the most to NOy, followed by NO3 − and HNO3, accounting for 87.5%, 10.5% and 2.0%, respectively, of NOy in Chengdu, and 91.4%, 6.9% and 1.7%, respectively, in Wanzhou. NH3 was the predominant contributor to NHx, contributing 65.6% and 72.2% in Chengdu and Wanzhou, respectively. Dry deposition fluxes were estimated using the inferential method with measured ambient concentrations and modelled dry deposition velocities. The total inorganic nitrogen dry deposition flux was estimated to be 21.4 and 8.5 kg N ha −1 yr −1, with 44.3% and 41.4% from NOy in Chengdu and Wanzhou, respectively. NO2 and NH3 each contributed about 80% of NOy and NHx dry deposition, respectively. Wet deposition was only collected in Wanzhou, where the annual wet deposition of NO3 − and NH4 + was 4.5 and 15.7 kg N ha −1 yr −1, respectively. The total wet plus dry deposition was 28.7 kg N ha −1 yr −1 in Wanzhou with 72.2% from reduced nitrogen. Therefore, controlling NH3 emissions from agricultural, traffic, waste containers and sewage system sources would be effective to reduce the total nitrogen deposition in the Sichuan Basin area. Graphical abstract: Highlights: Localized Vd was calculated with in situ land use and meteorological data in Sichuan Basin. NOy and NHx were both evidently higher in winter than in other seasons. High levels of NOy and NHx were caused by both the local emissions and long range transport. Reduced nitrogen was largely responsible for the total nitrogen deposition. Abstract : Ambient concentration and dry deposition budget of reactive nitrogen were first quantified in Sichuan Basin.